Chapter L'applicazione di tecniche innovative nel monitoraggio costiero degli habitat prioritari - Stocco, Rossella (Proceedings e report, 2020)
The aim of the present paper is to define the advantage to use innovative techniques based on sperimental tool to supplement the traditional techniques in marine monitoring, through experience of CRSM-ARPACAL (Centro Regionale Strategia Marina) into two regional projects called "SIC Carlit" and "Musmap". Both projects have shown that in the monitoring of coastal marine ecosystems the sperimental techniques to supplement traditional methods can provide more accurate and data with reduced costs and times of work.